Motoliango sebagai wujud Akuntansi di Upacara Tolobalango Gorontalo - Mohamad Anwar Thalib (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to understand accounting practices at the tolobalango ceremony. This research comes from concerns about the adoption, learning, and implementation of accounting which is not from Indonesia. This condition is getting worse with the lack of accounting studies based on national cultural themes. This situation has potential to eliminate accounting practices that are required by the values of local wisdom. Therefore, this research seeks to explore, formulate, and preserve accounting practices that live in the spirit of the nation's wealth values. This study uses an Islamic paradigm with an Islamic ethnomethodology approach. The results of the study find three ways in which the people of Gorontalo practiced accounting; firstly receiving wages; secondly receive dowry, wedding expenses, and consumption costs; the third record accounting in memory. These are based on the spirit of local wisdom in the form of sincerity (ihilasi), trustship (amana:ti), and trust (paracaya). This spirits are essentially a manifestation of love (motoliango) both among others and also to the Creator (God).